The influence of cultural values towards creativity enhancement: the case of Malaysian fashion designers / Mursyida Rosihan and Asliza Aris - Rosihan, Mursyida; Aris, Asliza (Faculty of Art & Design, 2022)
Malaysian fashion designers face difficulties and challenges in competing in the fashion industry due to the emerging international brands that exist in the market. Cultural values have influenced fashion designers in the process of design concept and use of textiles over time. This paper attempts to analyse the influence of cultural values on Malaysian fashion designer creativity and the elements that provide for creativity enhancement. The scope of this study was based on fashion designers located around the Klang Valley area. A qualitative approach is adopted using semi structured questions in an in-depth interview to gain an understanding of participants' cultural values, the design flow process, and product identity during their creative process. Using purposive sampling and snowballing technique, a sample of eight Malaysian fashion designers with a minimum of two years of design experience were interviewed. Participants were asked about the development experience, design process, creativity process, inspiration, experience of flow and product identity. The data was analysed using a constant comparison process. The findings suggest that cultural values and work environment have an indirect influence towards Malaysian fashion designers' creative design process. This study indicates that fashion designers' experiences serve as sources of inspiration that could be linked to creative design ideas and creativity. During the development process, solutions to the problems faced by the designer tend to emerge and as a result of the workflow, creativity is enhanced. The findings of this study provide insight on the relationship between Malaysian fashion designers' cultural values and experiences towards creative enhancement and in creative flow development which can assist them to be better prepared to compete in the local and global fashion industry. This study, however, finds a lack of focus on brand identity building amongst Malaysian fashion designers thus making them unnoticeable in the market.